Threshold traceability anonymous authentication scheme without trusted center for ad hoc network - Fang-bin LIU; Kun ZHANG; Hai LI; Hong ZHANG (Tongxin xuebao)
In order to provide anonymous authentication for ad hoc network,democratic group signatures with centerless secret sharing scheme and proposed a threshold traceability anonymous authentication scheme without trusted center for ad hoc network were combined.The scheme was centerless and self-organized,which was well suited to the characters of ad hoc network and had solved the problem that those schemes of traditional network were not suited to the ad hoc network.The prover of the scheme was anonymous,traceable,and complete,which well satisfied the security of anonymous authentication.